PEMANFAATAN GOOGLE TRENDS UNTUK MENGANALISIS POLA PENGGUNAAN MEDIA SOSIAL DI INDONESIA - Trilestari, Linda; Shovmayanti, Noor Afy; Kurniawan, Dani; Prakosa, Farid Aji (Jurnal Bincang Komunikasi, 2025)
This study examines social media usage patterns across Indonesia's regions using Google Trends as an analytical tool. By 2024, Indonesia's social media users reached 191 million (73.7% of the population), with platforms like Instagram, Facebook, and TikTok showing varying regional preferences influenced by demographic, geographic, and cultural factors. Employing a qualitative descriptive approach with secondary data from October to December 2024, the research explores regional and temporal trends in social media usage. The findings reveal Instagram's dominance in tech-savvy regions like Kalimantan Selatan, TikTok's popularity in expressive areas like Aceh and Sulawesi Barat, and Facebook's appeal among older demographics. The study underscores Google Trends' value in identifying regional behaviors, offering strategic insights for digital marketing. Higher education institutions can leverage these insights to optimize marketing by tailoring platform choices, content, and timing to local preferences. This approach enhances engagement and inclusivity while addressing digital disparities. The research contributes to strategic communication and emphasizes the importance of data-driven decision-making in fostering equitable digital outreach across Indonesia.